Unfair advantage - Kiyosaki, Robert T. 1947- (PTS Professional Sdn.Bhd, 2014)
This book is about real financial education. This book is about how debt and taxes make the rich richer &hellip and why debt and taxes makes the poor and middle class struggle. This book explains why the rich get richer, paying less in taxes, while the middle class shrinks &mdash with many losing jobs, homes, and retirement &mdash and paying more in taxes. This book is about the five unfair advantages a real financial education offers